Tocilizumab is clinically, functionally, and radiographically effective and safe either with or without low-dose methotrexate in active rheumatoid arthritis patients with inadequate responses to DMARDs and/or TNF inhibitors: A single-center retrospective cohort study (KEIO-TCZ study) at week 52. Issue 1 (January 2015) - Izumi, Keisuke; Kaneko, Yuko; Yasuoka, Hidekata; Seta, Noriyuki; Kameda, Hideto; Kuwana, Masataka; Takeuchi, Tsutomu
Abstract Objectives. To explore the effectiveness and safety of tocilizumab (TCZ) with or without methotrexate (MTX) in active rheumatoid arthritis (RA) patients showing inadequate responses to DMARDs and/or TNF inhibitors in clinical practice. Methods. We observed consecutive 115 RA patients initiating TCZ treatment in Keio University Hospital, dividing them into two groups with (TCZ + MTX group) or without MTX (TCZ group), and evaluated clinical, functional and structural outcomes besides safety at week 52. Results. Overall mean age, RA duration, and DAS28-ESR were 55.4, 8.4 years, and 5.0, respectively. Proportions of the prior use of TNF inhibitors and concomitant MTX were 45.5% and 57.4%, respectively. Mean dose of concomitant MTX was 8.4 mg/week. Baseline characteristics were comparable between the groups. TCZ improved disease activity measured by DAS28-ESR to 2.1 at week 52 overall, without significant difference between the groups. Clinical (DAS28-ESR < 2.6), functional (HAQ-DI ≤ 0.5), and structural (ΔTSS ≤ 0.5) remission rates in the TCZ group and the TCZ + MTX group were 79.1%/63.8% (P = 0.10), 62.8%/54.4% (P = 0.40), and 70.0%/53.8% (P = 0.61), respectively. Retention rates were 81.0% in the TCZ + MTX group and 88.5% in the TCZ group (P = 0.47). The rate of serious adverse events was comparable between the groups. Conclusions. TCZ was clinically, functionally, and radiographically effective and safe either with or without low-dose MTX.